PEMETAAN POTENSI WAKAF PRODUKTIF DI KOTA PEKANBARU - Astuti, Daharmi; Syamsul Bakhri, Boy; Masrayanti, Masrayanti (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2021)
This research is motivated by the lack of full implementation of productive endowments in Pekanbaru and the lack of management of productive waqf in Pekanbaru. The purpose of this study was to determine and analyze Productive Waqf Mapping in Pekanbaru. The theoretical framework used is Mapping theory with indicators of data collection stages, data presentation stages, and data use settings. The research method used is descriptive qualitative with data collection techniques using observation, interviews, documentation, literature study. The sample used is the saturated sample, the agency responsible for Productive mapping Waqf. This study indicates that Productive Waqf in Pekanbaru City has not been appropriately implemented due to the lack of people in productive earning and government participation to further optimize the empowerment of Waqf in Pekanbaru City in general. As for the Constraints and Obstacles of the Ministry of Religion in the process of Supervising Institution of Waqf in Pekanbaru City are: firstly, the lack of socialization budget for Productive Waqf, Secondly the Lack of Human Resources in managing Productive Waqf, Third Communities still think consumptive to be representative, fourth which became a reference in the city of Pekanbaru.